1992
DOI: 10.1007/bf00299391
|View full text |Cite
|
Sign up to set email alerts
|

An AP-1-like motif in the first intron of human Pro?1(I) collagen gene is a critical determinant of its transcriptional activity

Abstract: The first intron of the human Pro alpha 1(I) collagen gene contains an orientation-dependent enhancer composed of both positive and negative cis-acting elements involved in the transcriptional regulation of this gene. Deletion of a 360 bp Sau 3A intronic fragment spanning nucleotide +494 to +854 (S360) resulted in dramatic down-regulation of pCOL-KT (Thompson et al., J Biol Chem 266: 2549-2556, 1991). Using a DNaseI protection assay, we demonstrate a single footprint located at +590 to +615 in the S360 fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 33 publications
5
36
0
Order By: Relevance
“…Thus, these parallel pathways could converge at c-jun2TRE and cause hyperglycemic induction of c-jun expression. Our studies 1 incorporating a dominant-negative AP-1 construct (71) suggest that AP-1 activity is important for hyperglycemic up-regulation of collagen I expression, which is thought to involve AP-1 binding and transactivation (25,72,73). Therefore, suppression of c-jun expression by p38 inhibition should suppress collagen I expression, as we demonstrated in Fig.…”
Section: Fig 7 Hypertonicity Stimulates P38 Activation In Vivomentioning
confidence: 75%
“…Thus, these parallel pathways could converge at c-jun2TRE and cause hyperglycemic induction of c-jun expression. Our studies 1 incorporating a dominant-negative AP-1 construct (71) suggest that AP-1 activity is important for hyperglycemic up-regulation of collagen I expression, which is thought to involve AP-1 binding and transactivation (25,72,73). Therefore, suppression of c-jun expression by p38 inhibition should suppress collagen I expression, as we demonstrated in Fig.…”
Section: Fig 7 Hypertonicity Stimulates P38 Activation In Vivomentioning
confidence: 75%
“…In addition, the deletion tested in our study was a large one which very likely includes many potential cis-acting elements. Some of these elements have been tested individually or as part of shorter sequences in cell transfection studies, and both positively and negatively acting elements have been identified (2,6,26,29,33,34,52; see reference 8 for a review). The phenotype identified thus far in homozygous Col-Int⌬ mice may therefore reflect the net result of deleting multiple elements with opposing effects on transcription.…”
Section: Discussionmentioning
confidence: 99%
“…For supershift assays, nuclear extracts were preincubated with polyclonal antibodies against MyoD, myogenin, c-Myc, Max, USF-1, USF-2, or Sp-1 for 2 h at 4°C prior to initiation of the binding reaction. The contents of the binding reactions were electrophoresed at 4°C on a 4% nondenaturing polyacrylamide gel in 1 ϫ TBE (135 mM Tris, 45 mM boric acid, and 2.5 mM Na 2 EDTA, pH 8.9) and fluorographed; we have described EMSA methods in detail previously (50,51). All antibodies to transcriptional factors and the oligonucleotides containing the consensus recognition motifs used in EMSA were purchased from Santa Cruz Biotechnology, Inc.…”
Section: Methodsmentioning
confidence: 99%